The Relationship Between Leadership Style and Employee Psychological Well-Being at a Palm Oil Estate in Tawau, Sabah (Sains Humanika, 2023)
Strong leadership is the true cornerstone of an organisation and the backbone of a business. It has been suggested that the key role in ensuring success in the organisation and maintaining good psychological well-being is shared among employers and employees. Provision visualized that for maintaining a good psychological well-being among employees were shared between employers and employees the key in ensuring the success of maintaining good psychological well-being in the organisation. Hence, this study aims to explore the relationship between leadership style and employee psychological well-being at the palm oil estate in Tawau, Sabah.  Convenience sampling was adopted as a non-probability sample design in this investigation. There were 100 employees that participated in this study, which include the harvester, daily rate employees and line leader. The data collection was conducted by distributing the questionnaire using the Google Form as well in person. Questionnaires used in this research were Multifactor Leadership Questionnaire and Psychological Well Being Scale. The findings showed that the level of leadership style is at a moderate level, while the level of employee psychological well-being is at a high level. This study successfully found a relationship between leadership style and employee psychological well-being within the studied company. Sentence edit: Personal growth dimension was the highest score compared to other dimensionsThere are several limitations that occurred during the research. Firstly, the lack of ability to access the academic journal gave limitations to the researcher to conduct literature review and have a better understanding of the journals. In addition, this study only included one company located in Tawau. The results are not generalizable as the data only reflect one company. Future implications should highlight the importance of role models among leaders by exhibiting leadership style attributes when communicating with their employee as it may affect the employee’s perspectives towards them. Besides, allowing employees to recognize their potential, autonomy, and ideas is a great way to start the journey toward a better leadership style.
Keywords: Leadership style; Psychological well-being; Stress; Empowering; Quality of work life